Types and pedagogical functions of Amharic teachers' classroom speech acts - Kebede, Andualem; Endalamaw, Getachew (South African Journal of African Languages, 2025)
This study aimed to analyse the types and pedagogical functions of Amharic teachers' classroom speech acts. The subjects were two 10th-grade Amharic teachers at Debre Berhan Secondary School. The study employed a descriptive design with a qualitative method, gathering data through video recordings and observations. From the converted written data, a total of 1 241 teachers' utterances were analysed using the conversational analysis method. The study reveals that four types of speech acts, namely directives, assertives, expressives and commissives, were used by teachers. Directives were the most frequently used speech acts by teachers, constituting 55.92% of all utterances, followed by assertives (35.21%), expressives (7.74%) and commissives (1.13%). While directives aid in classroom management, an overreliance on them can hinder open discussions and language practice. Balancing the use of these speech acts is crucial for effective teaching. The pedagogical functions of the four types of speech acts were: the directives functioned as steering, controlling, and evaluating; the assertives as providing knowledge and controlling; the expressives as stimulating and encouraging; and the commissives as organising and planning functions. Understanding and utilising the different types and pedagogical functions of speech acts are vital for improving language learning outcomes and fostering successful teacher-student interactions.